O homem-máquina na cibercultura: análise teórico-crítica de signos de esportividade - Queiroz Neto, Valdemir Pereira de (2018)
This essay has as its main concern the insertion of the Critical Social Psychology in the contemporaneous debate about the sportivity as a signic value mediatized by the market, considering the experience of subjects in the usage and control of new technologies. In the cyberculture context, the sportivity cultural imperatives are problematized, reflecting on how subjetcs apropriate such values as a significant vector of production of their subjetivities. Therefore, we objet to analysethe way the sportivity signic value is used, in alliance with consumption and new technologies in the production of a man constituted through the ever- present hyertechnological machine. The thesis to be deffended is that the sportivity holds values socially worshiped/valued, it is projected in a profitable way and it mingles into human practices as an ideal rationalityto the purposes of the capitalistic exploitation directed to the machined-man. We revisit the Culture Industry discussion, updated with the concepts brought up from the cyberculture and social networks as a symbolic figure and producing source of new human constitutions, risingly mediated by technology. From the frankfurtian theoretical we aim at comprehending and analyzing thepersonal publicization in social networks, at present, constituted by the intensified interaction with the communicational and technological machines. Methodologicly, it is an empirical-theoretical research of qualitative nature and critical inspiration, in which we are guided by the Critical Theory proposal, whose micrological approach conceives the particular as a valuable index addressed to the whole scenario. This way, the sportivity phenomenom is elected for investigation as an index capable of disclosing a totality of cultural ideals relevant in contemporaneity. Through the sportivity prisma, we aim at establishing relations with work, leisure and consumption fields. In its development, firstly, current forms of scientifical productions are discussed and from the relations among instrumental rationality, technology e and human macinizing we explore concepts of technique and technology (Frankfurt School), updating this discussionwith contemporary authorsto display charecteristics of this historical construct defined as Man-chine.Afterwards, historical elemnets linked to sports are pointed outand its associations with market values found in contemporaneous signs sportivity and we describe cyberspace and technocultural aspects as a field of interactive communication among subjects and virtual networks. Thus, we object an analysis on the occupation of this virtual ambience, which is result of the great advances in Communication and Information technologies, via sportivity signs as ideals of performanceof the contemporary human. In our analysis, we have described social networks focused on physical and sports activities, non-sports-like leisure activities, technological sociability activities and work activities. We have arranged the presentation of the sportivity signs divided into category groups named 1) serious games; 2) spectacle of sportivized machines; 3) sacrifices and pain devotion; 4) Badges of rankings, records and deeds. This way, from a theoretical-critical analysis, we search for a contribution to the reflection on ethical and psychosocial implications of the current adoption of the sportivity ideal to various espheres of human life.